PERBEDAAN TINGKAT KECEMASAN DENTAL PADA MURID SMU BERDASARKAN KARATERISTIK SOSIODEMOGRAFI (Universitas Tarumanagara, 2022)
Dental anxiety is a condition when someone feels anxious about dental and oral treatment. Dental anxiety causes patients to avoid dental and oral treatments, thereby increasing the risk of dental and oral health problems. This study aims to determine the differences in the level of dental anxiety in high school students based on sociodemographic characteristics. In this online cross sectional study, a total of 145 students of Loyola College Semarang was participated. Dental anxiety was assessed using Short Dental Anxiety Inventory (S-DAI) questionnaire which consisted of 9 statements. Mann-Whitney test was performed to measure dental anxiety mean score differences. Chi-Square test was conducted to see the associations between dental anxiety level and sociodemographic characteristics. As many as 60% students had mild to moderate dental anxiety, while 32% students had severe dental anxiety. Students who had never visited a dentist in the past year had higher mean scores (25.14 + 8.39;p=0.022) compared to students who visited a dentist once or more during the past year (21.37 + 8.61). There was significant difference in the mean value of dental anxiety in Loyola College Semarang high school student based on visits to the dentist in the past year. Keywords: dental anxiety; S-DAI; high school student AbstrakKecemasan dental merupakan suatu keadaan seseorang merasa cemas terhadap tindakan perawatan gigi dan mulut. Kecemasan dental menyebabkan pasien menghindari perawatan dokter gigi, sehingga meningkatkan risiko masalah kesehatan gigi dan mulut. Penelitian ini bertujuan mengetahui perbedaan tingkat kecemasan dental pada murid SMU berdasarkan karateristik sosiodemografi. Penelitian cross sectional ini dilakukan secara daring pada 145 murid SMU Kolese Loyola Semarang. Pengukuran kecemasan dental menggunakan instrumen kuesioner Short Dental Anxiety Inventory (S-DAI) yang terdiri dari 9 pernyataan. Uji Mann-Whitney dilakukan untuk melihat perbedaan nilai rata-rata kecemasan dental murid. Uji Chi-Square dilakukan untuk melihat hubungan antara tingkat kecemasan dental dengan karateristik sosiodemografi murid. Sebanyak 60% murid memiliki kecemasan dental dalam tingkat ringan sampai dengan sedang, sementara 32% murid memiliki kecemasan dental berat. Kelompok murid yang tidak pernah mengunjungi dokter gigi selama satu tahun terakhir memiliki nilai rata-rata lebih tinggi secara signifikan (25,14 + 8,39; p=0,022) dibandingkan dengan kelompok murid yang mengunjungi dokter gigi sebanyak satu kali atau lebih selama satu tahun terakhir (21,37 + 8,61). Terdapat perbedaan nilai rata-rata kecemasan dental yang bermakna pada murid SMU Kolese Loyola Semarang berdasarkan kunjungan ke dokter gigi dalam satu tahun terakhir.